ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL STATEMENT FRAUD PADA SATUAN KERJA PERANGKAT DAERAH KOTA PEKANBARU - Indra, Mhd. Ricky; Hasan, Amir; ', Al Azhar A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine and analyze the effect of enforcement, the effectiveness of internal control, information asymmetry, distributive justice, procedural justice, organizational commitment and ethical culture of the tendency of fraud (fraud) At the Regional Work Units Pekanbaru. The population covers all aspects related to the preparation of financial statements in government agencies located in the city of Pekanbaru. The population in this study consisted of all SKPD contained in Pekanbaru city as much as 32 SKPD. Each SKPD will be spread as much as 3 questionnaire consisted of Chief SKPD, Head of Finance and Head of the planning of each SKPD contained in Pekanbaru, bringing the total respondents were 96 respondents, but the number of returnees and deserves to be tested as many as 52 respondents. Further analysis of data using multiple regression analysis through SPSS 17.0 software msi. It can be concluded that the enforcement of legislation, the effectiveness of internal control, information asymmetry, distributive justice, organizational commitment and ethical culture of the organization significant effect on the tendency of fraud (fraud) At the Regional Work Units Pekanbaru. While no effect was Procedural Justice against the trend of fraud (fraud) At the Regional Work Units Pekanbaru.Keywords: Factors Affecting Financial Statement Fraud